Performance Analysis of 100 KVA Generator Set as AC Backup Supply at Panakukang Electrical Substation - Muh. Imran Bachtiar; Andi Wawan Indrawan; Muammar Abidin; Syarifuddin Nojeng; Mochammad Apriyadi Hadi Sirad (Universitas Khairun, 2026)
Substation AC backup supply reliability is critical for sustaining auxiliary equipment operation during grid blackouts. Prior studies on genset sizing and motor starting have not specifically addressed substation AC backup systems integrating continuous loads, non-continuous motor loads, and comparative starting methods. This study evaluates the adequacy of the existing 100 kVA prime / 110 kVA standby genset at Panakkukang Substation using field data collection and ETAP 19.0.1 simulation. The total continuous load is 9.342 kW, requiring a minimum genset capacity of 11.675 kW after applying a 46.7% demand factor and 125% safety factor (per NFPA 110 and ISO 8528-1). The existing genset adequately covers continuous loads at only 10.62% of standby capacity. However, simultaneous starting of the hydrant and oil pump motors exceeds genset capability under all methods tested: Direct-On-Line (DOL) causes a 24.00% voltage dip requiring 463.74 kVA; Wye-Delta reduces voltage dip to 17.48% requiring 231.87 kVA; and VFD limits voltage dip to below 3% requiring only 159.17 kVA, compliant with IEEE Std 1159-2019. This study recommends upgrading genset capacity to at least 160 kVA and adopting VFD motor starting to ensure reliable substation AC backup supply.